Reading Literacy Preferences of Indonesian Language and Literature Education Students - Ramdhani, Marlinda (Lembaga Penelitian dan Pendidikan Mandala, 2024)
This study was conducted to analyze the preferences of reading literacy types and media of Indonesian language and literature education students, Faculty of Teaching and Training Education, University of Mataram. This study is a qualitative study and is included in the type of single case study research. The data of this study are the types of non-subject reading books and types of reading media used by students in developing their reading literacy culture. The data sources of this study are students' daily reading journals and interview results. The results of the study show that the types of non-subject books that students have read are novels, Wattpad, poetry, motivational books, and comics, while the media used by students to read are physical and digital books..